1992
DOI: 10.1111/j.1365-2362.1992.tb01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the new somatostatin analogue (BIM 23014) on blood glucose homeostasis in normal men

Abstract: Changes in blood glucose homeostasis induced by the new somatostatin analogue BIM 23014 (BIM) were studied. Eight normal men (study 1) received either vehicle or 1000, 2000 and 3000 micrograms BIM as a 24 h s.c. infusion. Blood glucose, plasma insulin, C-peptide, glucagon and growth hormone (GH) were measured before treatment and then hourly for 24 h. In five normal men (study 2) an oral glucose tolerance test (OGTT) was performed during vehicle infusion and then on days 1 and 7 of a continuous s.c. infusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…1). In 3 patients mean GH in multiple sampling was below 5 pg/ I; however, in only 1 of them was GH reduced to less than 2^g /1 during OGTT. In 5 out of 7 patients who demonstrated a sustained reduction in GH during the therapy the TRH injection stimulated a paradoxical increase of GH before treatment.…”
Section: Control Of Gh Axismentioning
confidence: 92%
See 1 more Smart Citation
“…1). In 3 patients mean GH in multiple sampling was below 5 pg/ I; however, in only 1 of them was GH reduced to less than 2^g /1 during OGTT. In 5 out of 7 patients who demonstrated a sustained reduction in GH during the therapy the TRH injection stimulated a paradoxical increase of GH before treatment.…”
Section: Control Of Gh Axismentioning
confidence: 92%
“…In previous studies BIM 23014 proved to be a useful tool in selectively inhibiting GH secretion (1)(2)(3). The effects of the slow-release formulation of the product have been reported in a limited number of patients with treatment period not exceeding 12 months (4-6).…”
mentioning
confidence: 98%
“…The healthy subjects had a more homogeneous distribution of GLP-1 and insulin concentrations and their GLP-1 and insulin escape was already significant in the St-M after only 1 week of treatment. An early escape of insulin and lack of GH escape have also been found during treatment with the somatostatin analog BIM 23014 (18).…”
Section: European Journal Of Endocrinology (1999) 140mentioning
confidence: 95%
“…GH counteracts the effects of insulin by inhibiting the phosphorylation of the insulin receptor. Moreover, GH also inhibits the phosphorylation of one of the proximate molecules of the insulin signaling cascade, insulin receptor substrate-1 in response to insulin (Kuhn et al 1992). In acromegaly, several studies have shown that increased GH induces insulin resistance (Kasayama et al 2000).…”
Section: Influence Of Lanreotide Autogel® On Clinical Manifestationsmentioning
confidence: 99%
“…The acute effects of subcutaneously infused lanreotide were studied in healthy subjects. Oral glucose tolerance worsened during the first day of administration, but was restored on day 7 while drug administration continued (Kuhn et al 1992). In a study in 27 patients the homeostasis model assessment (HOMA) index improved, but not the quantitative insulin check index (QUICKI) index (Ronchi et al 2003).…”
Section: Influence Of Lanreotide Autogel® On Clinical Manifestationsmentioning
confidence: 99%